1998
DOI: 10.1191/095968398666496051
|View full text |Cite
|
Sign up to set email alerts
|

Experimental production and analysis of microscopic charcoal from wood, leaves and grasses

Abstract: Study of microscopic charcoal from lake sediments has led to a greater understanding of past veg etation, climate and fire ecology. We investigated the potential of charcoal morphology as an indicator of vegetation type. Grasses, leaves and wood were burned under controlled conditions in the laboratory, and we used a dissecting scope, video camera, and image-capture software to image-sieved (125-μm screen) micro-scopic charcoal. Charcoal from grasses was significantly longer (562 μm) and had a greater length:w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 20 publications
7
134
1
2
Order By: Relevance
“…The elongation degree is preserved even when the particle is broken (24). Experimental analysis conducted on burned grasses and wood from North America showed that charcoal from grasses has a greater elongation ratio than charcoal derived from wood (24). We thus infer that the increase in the mean elongation of microcharcoal particles is an indicator of low-intensity fires spreading in grass-dominated fueled environments.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The elongation degree is preserved even when the particle is broken (24). Experimental analysis conducted on burned grasses and wood from North America showed that charcoal from grasses has a greater elongation ratio than charcoal derived from wood (24). We thus infer that the increase in the mean elongation of microcharcoal particles is an indicator of low-intensity fires spreading in grass-dominated fueled environments.…”
Section: Resultsmentioning
confidence: 86%
“…During a fire, charcoal fragmentation occurs along axes derived from the anatomical structure of plant species. The elongation degree is preserved even when the particle is broken (24). Experimental analysis conducted on burned grasses and wood from North America showed that charcoal from grasses has a greater elongation ratio than charcoal derived from wood (24).…”
Section: Resultsmentioning
confidence: 99%
“…Dans les sols minéraux secs, les reliques paléobotaniques correspondent à des pièces carbonisées résultant de feux récurrents sur de longues périodes (Carcaillet, 1998 ;Talon, et al, 1998). Bien que les feuilles, les stomates, les cônes ou leurs écailles et les rameaux soient d'excellents éléments pour la détermination des assemblages d'espèces de conifères (Dunwiddie, 1987 ;Umbanhowar et McGrath, 1998) (Payette et Filion, 1975 ;Payette, 1983), les facteurs historiques demeurent méconnus. La distinction des restes de mélèze serait aussi essentielle pour établir sa limite passée en Hudsonie (Gagnon et Payette, 1981) et pour suivre dans le temps son patron de migration dans la péninsule du Qué-bec-Labrador.…”
Section: Introductionunclassified
“…A further question arising from such morphometric studies is the extent to which particle morphology is infl uenced by the method by which larger charcoal pieces have been broken down. Charcoal crushed in a mortar and then sieved, as in Umbanhowar and McGrath (1998) , may display different morphological features compared to that broken down by natural processes. simulated the effects of bedload transport by placing charcoal produced from Pinus sylvestris L. twigs, sieved to between 3.3 and 9.5 mm, with sand and water http://www.bioone.org/loi/apps Particles of less than 315 μ m 2 or greater than 1,000,000 μ m 2 were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We have subjected charcoal particles derived from a range of plant materials to a realistic method of breakdown, with the aim of establishing whether different fuel types undergo distinctive changes in morphology under increasing degrees of breakdown. We also further test the hypothesis of Umbanhowar and McGrath (1998) that the aspect ratio of charcoal particles can reveal whether they originate in grassland or woodland fi re.…”
mentioning
confidence: 99%